Kreativitas Pondok Pesantren As-Salafiyah Mlangi dalam Mengadopsi Sistem Pembelajaran Model Kampus - Muhammad Minanurrofiq; Almer Hasan Slamet Saputra (IIQ An Nur Yogyakarta, 2022)
Looking at the progress of time, there have been many changes in both learning and teaching aspects, starting from government policies that constantly change in terms of curricula to the policies regarding the national examination system. This applies to both public and private schools, Islamic boarding schools (pesantren), universities, and so on. However, educational institutions will not deviate from what has been set by the Ministry of Education or the Ministry of Religious Affairs. These policies continue to serve as guidelines in the implementation of the educational system. Educational institutions in Indonesia are not only limited to formal schools and universities but also encompass pesantren, whose existence contributes to the diversity of the educational system in Indonesia. One of these pesantren is As-Salafiyah Mlangi, which is located at the following address: Jalan Kiai Masduqi, Mlangi, Nogotirto, Kec. Gamping, Sleman Regency, Special Region of Yogyakarta, 55592